(untitled) (CIPEEX, 2025)
Depression can be conceptualized as a chronic mood disorder characterized by feelings of sadness, difficulty concentrating, irritability, indisposition and other symptoms, which have negative consequences for the individual’s life. Pharmacological therapy is essential to treat these disorders, with pharmacists playing a crucial role in treatment adherence. The aim of this study was to carry out a literature review highlighting the role of pharmacists in patients with depression and in the rational use of psychotropic drugs. A search was made for articles in the Scielo, PubMed and Virtual Health Library databases. To search for articles, the following terms were selected: pharmacist, depression, management and medicines. The search was limited to articles published in the last five years, in Portuguese. As a result, four articles were selected for this study. Challenges related to accessibility to effective, quality healthcare were identified. Pharmacological treatment, which uses psychotropic drugs to manage symptoms, requires specific care and detailed guidance. Technical support is essential to prevent intoxication and addiction resulting from the inappropriate use of these drugs. In this context, the role of pharmacists in mental health is indispensable. Recognized as drug specialists, these professionals have the ability to provide expert advice, promoting the rational use of drugs and contributing to patients’ quality of life. Therefore, the importance of pharmacists in the management of psychotropic drugs in patients with depression is highlighted, as well as the need for public policies that raise awareness of the risks of using these drugs without proper professional monitoring worker.